Hoax News: Promoting the Studentsâ Critical Thinking in Critical Reading Class - Haryati, Sri; Hidayati, Diyah Nur (Register Journal, 2017)
Critical thinking is vital for graduates in facing the dynamic life in order to strengthen their analysis ability and providing alternative solution towards the current problem. It is essential that units, courses, and material teach the critical thinking process have to provide an opportunity for students to excoriate certain problem and present the harmonious flow of thinking. Hoax news, the trending issue in a society as the reading materials, has abundance aspect to be criticized by students. Moreover, it has its own authenticity to be brought into a critical reading class as authentic materials which was not broadly discussed yet. This study aimed at paving the ways to improve the studentsâ critical thinking skills through reading hoax news. It is conducted to investigate the usage of hoax news in teaching critical reading for undergraduate students as well as particularize how far hoax news can enhance studenstâ critical thinking. This study employed classroom action research design. The subject of the study was the 31 students joining the critical reading class. The data were gotten from observation, document analysis and test. The essay test was the instrument used to assess the studentsâ critical thinking which later adopted the model of the Holistic Critical Thinking Scoring Rubric (HCTSR). The result of the study showed that using of hoax news significantly improve the studentsâ critical thinking followed by the development of interpretation, analysis and identification ability. The number students posed strong thinking increased from 6.45% to 72,2%. Using critical thinking can promote studentsâ high order thinking since it drives students to consider the fact and fake which demanding the high analysis and deep interpretation toward the presented text.Â  Â Keywords: Critical thinking, hoax news, teaching materials.Â INDONESIAN ABSTRACTÂ Berpikir kritis merupakan hal yang penting dalam mengahadapi hidup yang dinamis untuk memperkuat kemampuan analisis serta memberikan alternatif solusi dalam memecahkan masalah yang dihadapi saat ini. Sangatlah penting dalam setiap unit pembelajaran, perkuliahan dan materi mengajarkan prosesÂ  berpikir kritis untuk menyiapkan siswa dalam menghadapi berbagai masalah dan merepresentasikan pemikiran secara runtut. Hoax News (Berita Hoax), permasalahan aktual di masyarakat, sebagai bahan bacaan menyuguhkan berbagai aspek untuk siswa kritisi. Terlebih, berita hoak mempunyai nilai autentik untuk dapat digunakan di kelas critical reading sebagai materi otentik yang belum banyak dibahas. Penelitian ini bertujuan untuk mengungkapkan cara meningkatkan berpikir kritis siswa dengan menggunakan hoax news sebagai bahan bacaan. Selain itu, penelitian ini berupaya mengungkap penggunaan berita hoak dalam mengajarkan kritikal reading bagi siswa serta mengetahui seberapa jauh berita hoal dapat meningkatkan kemampuan berpikir kritis siswa. Penelitian ini menggunakan desain penelitian tindakan kelas. Data diperoleh dari observasi, analisis dokumen dan tes. Tes berbentuk uraian (essay) merupakan instrumen penelitian yang digunakan untuk mengukur tingkat berpikir kritis siswa yang mana rubric penilaian model Holistic Critical Thinking Scoring Rubric (HCTSR) diadopsi untuk keperluan ini. Pengamatan juga dilakukan untuk mendukung perolehan data dalam penelitian ini. Hasil penelitian menunjukkan bahwa penggunaan hoax news secara signifikan dapat meningkatkan tingkat berpikir kritis siswa yang diikuti dengan meningkatnya kemampuan interpretasi, analisis dan identifikasi. Jumlah siswa yang memiliki kemampuan berpikir kritis yang kuat meningkat dari 6.45% menjadi 72,2%. Menggunakan berita hoak dapat meningkatkan kemampuan berpikir kritis karena materi ini memacu siswa untuk berpikir kritis dan melakukan analisa mendalam pada teks yang disajikan. Kata kunci: berfikir kritis, berita Hoax, materi mengajar